PERTUMBUHAN DAN PERKEMBANGAN PESERTA DIDIK SECARA SOSIAL STUDENTS’ DEVELOPMENT ON SOCIAL ASPECT - Ekowati; Suryana (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
At the beginning of mankind has not been born a social nature, in the sense of not having the ability to interact with others. Child's social ability is obtained from a variety of opportunities and experiences people associate with their environment. The need to interact with other people has been felt since the age of six months, when they have been able to get to know another human being, especially the mother and her family members. Children begin to distinguish the meaning of a smile and other social behaviors, such as anger (not happy to hear loud noises) and affection. Social development in adolescence develops the ability to understand another person as a unique individual. Both related to personal traits, interests, values or feelings that encourage teens to socialize more familiar with the peer environment or society either through friendship or romance. At this time berkembangan attitudes tend to give up or to follow the opinion, opinions, value, habits, interests, desires of others. There adolescent social environment (peers) that displays an attitude and behavior that can be justified, for example: pious, noble character, and others. Teens are expected to have appropriate social adjustment in terms of the ability to react appropriately to social reality, situations and relationships both within the family, school and community